On the uniqueness of the unital divisor of a matrix polynomial over an arbitrary field - Prokip, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Conditions are established under which the unital divisor extracted from a matrix polynomial over an arbitrary field is determined uniquely by its characteristic polynomial. The result obtained is applied to the problem of solving matrix polynomial equations.